2002
DOI: 10.1111/j.1365-2621.2002.tb08710.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Postharvest Putrescine Treatment on Extending Shelf Life and Reducing Mechanical Damage in Apricot

Abstract: Apricots (Prunus armeniaca L. cv Mauricio) harvested at commercial ripening stage were treated with putrescine (1 mM), then mechanically damaged with a 25 N force and stored at 10 °C for 6 d. Putrescine treatment increased fruit firmness and reduced the bruising zones caused by the mechanical damage. Putrescine-treated fruits (both damaged and nondamaged) showed different physiological behavior than controls. Color change, weight loss, ethylene emission, and respiration rate were reduced in putrescine-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 27 publications
(10 reference statements)
8
64
1
2
Order By: Relevance
“…The lowest weight loss was observed in Put+ultrasound-treated fruits (7.6%) and followed by control fruits (8.0%). Weight loss findings in this study were not similar to those for apricot by Martínez-Romero et al (2002) and plum by Serrano et al (2003), who found that Put showed significantly less weight loss as compared with untreated fruits. These different results may be explained by different physiological features of experimental materials and different storage conditions.…”
Section: Weight Losscontrasting
confidence: 99%
See 1 more Smart Citation
“…The lowest weight loss was observed in Put+ultrasound-treated fruits (7.6%) and followed by control fruits (8.0%). Weight loss findings in this study were not similar to those for apricot by Martínez-Romero et al (2002) and plum by Serrano et al (2003), who found that Put showed significantly less weight loss as compared with untreated fruits. These different results may be explained by different physiological features of experimental materials and different storage conditions.…”
Section: Weight Losscontrasting
confidence: 99%
“…Exogenously applied Put reduced fruit deterioration and increaseed shelf life of lemon (Citrus limon [L.] Burm. f., Martínez-Romero et al, 1999), apricot (Prunus armeniaca L., Martínez-Romero et al, 2002), sweet cherry (Prunus avium [L.] L., Bal, 2012), strawberry (Fragaria ×ananassa Duchesne ex Rozier, Khosroshahi et al, 2007), and plum (Prunus salicina Lindl., Perez-Vicente et al, 2002;Khan et al, 2008). Plums treated with 1 mM Put showed delayed and reduced ethylene production together with higher fruit firmness, lower soluble solutions and titratable acids, reduced weight loss, and delayed color change, which led to extended storage life Serrano et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Spm or Spd treatment retarded softening of apple 37 and strawberry fruits 61 . Exogenously applied Put resulted in a reduction of mechanical damage and an increase in firmness of lemon 48 , apricot 49 and plum 59 . Polyamines added exogenously reduced or delayed browning, peroxide level and ethylene production, coupled with elevated levels of polyamines in litchi fruits stored at 5 o C 32 .…”
Section: Use Of Exogenous Polyamines In Postharvest Managementmentioning
confidence: 95%
“…In this regard, it is proposed that they have different effects on regulation of fruit ripening, ethylene being stimulatory and polyamine inhibitory. Therefore, it is possible to regulate and control ethylene evolution by exogenous application of polyamine, which has been tried in apple 1 , peach 10 , litchi 32 , apricot 49,55 , plum 59 , Tradescantia 79 , nectarine 83 , and avocado 91 . Exogenous application of polyamine delayed softening of peach 10 and apple 37 fruits on the tree as well.…”
Section: Relationship Between Polyamine and Ethylenementioning
confidence: 99%
“…Polyamines were also shown to maintain flesh firmness in apples (Kramer et al 1989(Kramer et al , 1991Wang et al 1993), strawberries (Ponappa et al 1993), tomatoes (Law et al 1991), lemon (Valero et al 1998a, b, c), peach (Bregoli et al 2004) and plum (Serrano et al 2003). The treatment with exogenous polyamines has been reported to delay colour changes, reduce mechanical damage and chilling injury susceptibility and increase shelf life in both climacteric and non-climacteric fruits (Serrano et al 1996;Martinez-Romero et al 2002;PerezVicente et al 2002).…”
Section: Introductionmentioning
confidence: 99%